Plasma‐assisted deposition of fungicide containing coatings for encapsulation and protection of maize seeds. Issue 6 (26th March 2019) - Lo Porto, Chiara; Palumbo, Fabio; Somma, Stefania; Masiello, Mario; Moretti, Antonio; Fracassi, Francesco; Favia, Pietro
Abstract: The aim of the research work here reported is to illustrate how to incorporate prothioconazole, a molecule with fungicide action, in plasma‐deposited polymeric coating, encapsulating maize seeds. With this approach, high fungicide effect with a small quantity of chemicals and less pollution of soil and water should be achieved. The fungicide composite coating is composed of three layers: a hydrophilic plasma deposited polymeric layer to increase the wettability of the seed surface; a layer of sprayed prothioconazole aqueous solution; and a hydrophobic plasma deposited barrier layer to limit leaching and mimic the natural seed wettability. The application of the composite coating is found not to interfere with the germination of the seeds, while the percentage of maize crowns infected by Fusarium graminearum was successfully reduced from 94% in the control to none in the coated seeds. Abstract : For the first time the plasma deposition of an active coating for protecting seeds against fungi is reported. Prothioconazole is embedded in a plasma polymerized coating wrapping maize seeds, susceptible to fungi attack. With this approach, a high fungicide effect with small quantity of antifungal molecule and potentially less pollution of the surrounding environment has been achieved.